Student Leader Burnout at Christian Universities: The Protective Roles of Achievement and Awareness of God - Gibson, Daniel (Christian higher education, 2025)
Many leaders increase their risk of burnout, the strain from exposure to job-related stress, by neglecting to adequately care for themselves, especially as they experience conflict between the roles they perform and a lack of clarity around the limits of their responsibilities. Resident Assistant (RA) positions are often ambiguous and ill-defined, encompassing roles as helping professionals, administrators, and spiritual leaders for their residents at all hours of the day, navigating conflicting demands placed on them by their myriad responsibilities while also being students themselves. The role conflict and ambiguity they are exposed to have increased in recent years as the scope of RA positions continues to expand, heightening role conflict and ambiguity. This study collected surveys of RAs at a Christian university in the southwest United States to determine the effects of one’s sense of personal accomplishment and spirituality on burnout and its facets of emotional exhaustion, a marked lack of emotional and physical energy, and depersonalization, a dehumanizing perception that distances self from others. Findings indicate that high levels of personal accomplishment, when paired with a strong awareness of God, mitigate the risk of burnout by attenuating the relationship between emotional exhaustion and depersonalization. This extends current understandings of protective factors that can inform efforts to prevent burnout and promote well-being in RAs and other spiritual leaders.